Structural and Mutagenesis Studies of the Thiamine-Dependent, Ketone-Accepting YerE from Pseudomonas protegens - Hampel, Sabrina (2018)
A wide range of thiamine diphosphate (ThDP)‐dependent enzymes catalyze the benzoin‐type carboligation of pyruvate with aldehydes. A few ThDP‐dependent enzymes, such as YerE from Yersinia pseudotuberculosis (YpYerE), are known to accept ketones as acceptor substrates. Catalysis by YpYerE gives access to chiral tertiary alcohols, a group of products difficult to obtain in an enantioenriched form by other means. Hence, knowledge of the three‐dimensional structure of the enzyme is crucial to identify structure–activity relationships. However, YpYerE has yet to be crystallized, despite several attempts. Herein, we show that a homologue of YpYerE, namely, PpYerE from Pseudomonas protegens (59 % amino acid identity), displays similar catalytic activity: benzaldehyde and its derivatives as well as ketones are converted into chiral 2‐hydroxy ketones by using pyruvate as a donor. To enable comparison of aldehyde‐ and ketone‐accepting enzymes and to guide site‐directed mutagenesis studies, PpYerE was crystallized and its structure was determined to a resolution of 1.55 Å.